Kompetencje państw członkowskich Unii Europejskiej w obszarze regulacji organizmów genetycznie zmodyfikowanych: [The powers of EU Member States in the field of genetically modified organisms’ (GMO) regulation] (Studia Prawnicze / The Legal Studies, 2006)
Pierwsze horyzontalne wiążące wspólnotowe akty prawne dotyczące organizmów genetycznie zmodyfikowanych (GMO) i ich wykorzystania przyjęte zostały w 1990 r. Od tej pory wspólnotowe unormowania w tym obszarze podlegały ciągłej ewolucji i były przedmiotem ożywionej debaty. Kontrowersje i obawy związane z wykorzystaniem GMO nasiliły się pod koniec lat dziewięćdziesiątych. Skutkiem spadku akceptacji w poszczególnych państwach członkowskich Unii Europejskiej dla wprowadzania do obrotu i stosowania produktów nowoczesnej biotechnologii było kilkuletnie moratorium na GMO. Wspólnotowe procedury aprobowania nowych GMO zostały całkowicie zablokowane. W poszczególnych państwach członkowskich ustanowiono szereg restrykcji i barier będących wyrazem ogólnej polityki braku akceptacji dla GMO. Reperkusją opisanej sytuacji było złożenie na forum Światowej Organizacji Handlu (WTO) przez państwa zainteresowane eksportem produktów biotechnologicznych na rynek wspólnotowy (Stany Zjednoczone, Kanadę oraz Argentynę) skarg skierowanych przeciw ko Wspólnocie i jej państwom członkowskim i zapoczątkowanie przewidzianej w systemie WTO procedury rozstrzygania sporów.  Division of powers between the European Community and its Member States in the field of genetically modified organisms’ regulation is a complex issue, requiring a thorough, detailed analysis of primary as well as of secondary law provisions. At the Community level a number of important legał acts referring to GMO and their use have been adopted, among which the central place takes a horizontal directive no. 2001/18. To determine the impact which the Community legał acts referring to GMO have on Member States’ powers in this area of regulation it is essential to analyse the legał basis of the mentioned acts, their objective and content, and finally - the degree and scope of harmonization achieved at the EC level under these acts. Despite the recent revision of Community legał regime on GMO and the adoption of several new legał acts in this field the controversies and lack of certainty with regard to placing of GMO on the Community market persist. Individual Member States (as well as their regions) are exploring the possibilities under the EC law to pursue a level of environmental and human health protection that is higher that the level deemed appropriate at the EC level and to prohibit or restrict the free circulation and use of GMO and GM products within their territory. Under the primary law the most important provisions which ought to be analysed in this context are contained in article 95 of the EC Treaty. In order to provisionally derogate from the Community provisions individual Member States may invoke the safeguard mechanism established under EC secondary law. In this study a thorough analysis of these provisions and conditions which must. be fulfilled to invoke them in order to introduce national protective measures has been conducted. Co-existence of genetically modified crops with conventional and organie farming, appropriate regulation of the issue and Member States’ powers in this field are also worth analysis. The revision of Community legał regime on GMO has been pointed out by the Member States as the prerequisite for pulling an end to the so-called “de facto moratorium” and for overcoming the decision-making impasse with regard to placing GMO and GM products on the EC market and their use within the Community. However, many issues have not been resolved yet and they are a subject of intense debate at various levels (regional, State and Community), especially in context of the complaints filed by the United States, Canada and Argentine and the dispute settlement proceedings initiated against the European Community and its Member States in the World Trade Organisation (WTO) in the matter of EC biotechnology measures. Conseąuently, further comprehensive and detailed discussion is essential to ensure effectiveness, transparency and coherence of this sensitive field of regulation and to provide the balance between the double objective pursued at the EC level: establishment of high level of environmental and human health protection as well as providing smooth, undistorted functioning of the EC intemal market and safe development of modem biotechnology.